2023
DOI: 10.3390/plants12040903
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Traits of Interest in Apple Breeding and Their Implications for Selection

Abstract: Apple breeding is a laborious and long-lasting process that requires qualified resources, land, time, and funds. In this study, more than 5000 F1 apple hybrids from direct and testcrosses were analyzed. The results revealed how the phenotypic expression of the main quantitative traits of interest assessed in five half-sib families was controlled by the additive genetic effects and by non-additive effects of dominance and epistasis. The statistical number of hybrids required to ensure efficient selection increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…The new cultivars obtained are primarily intended for use in parks, gardens, and as cut flowers, and they offer a wide range of colour, form, scent, recurrent blooming and hardiness combinations. Even though there are various methods of inducing artificial variability, the primary breeding method used for all species, was artificial hybridization, followed by selection, which resulted in positive outcomes for both rose and other Rosaceae species (Wagner et al, 2000;Sestras and Sestras, 2023).…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The new cultivars obtained are primarily intended for use in parks, gardens, and as cut flowers, and they offer a wide range of colour, form, scent, recurrent blooming and hardiness combinations. Even though there are various methods of inducing artificial variability, the primary breeding method used for all species, was artificial hybridization, followed by selection, which resulted in positive outcomes for both rose and other Rosaceae species (Wagner et al, 2000;Sestras and Sestras, 2023).…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Humidity depends on precipitation, temperature, local terrain characteristics (soil type or slope-impact infiltration rate of precipitation in soil), and the vicinity of the sea. These, and other, limitations are considered as risks, and in some cases could be manageable using agrotechnical measures and selection of more resistant varieties [43,44]. In [13] it is shown that the significant increase in temperature conditions, expansion of growing season, but also the increase in precipitation will happen in the future in Norway.…”
Section: Discussionmentioning
confidence: 99%
“…Nak., and P. sinkiangensis T.T.Yu have been recorded in China. In addition, just like with apples [ 30 ], vegetative multiplication and the extension of different clones, heirlooms, and mutations of the same cultivar, each with its own unique local or regional names, synonyms, and homonyms [ 4 , 12 , 31 , 32 ], are likely to make the total number of cultivated forms considerably higher than has been thought.…”
Section: Introductionmentioning
confidence: 99%
“…The Horticulture Research Station in Cluj-Napoca, Romania, situated in the country’s northwest, achieved remarkable results in fruit tree breeding, releasing many cultivars [ 27 , 46 ]. However, breeding cultivars with a desired associated response to the attack of different biotic stress agents is extremely difficult in fruit trees [ 27 , 30 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation